Pengaruh Kualitas Layanan Pendidikan Terhadap Kepuasan Peserta Didik Kelas XII Di Madrasah Aliyah Negeri 2 Karawang - Alif, Khairunnisa Putri (El-Idare, 2021)
This article discusses the effect of the quality of educational services on the satisfaction of class XII students at Madrasah Aliyah Negeri 2 Karawang. This type of research is quantitative with a descriptive approach. The sample in this study were 103 students of class XII. Analysis of the data used is descriptive statistics and classical assumption test (test requirement analysis) by performing normality test, linearity test. Subsequently, hypothesis testing was carried out by calculating the correlation coefficient, coefficient of determination, significance level, and regression analysis. The results showed that the quality of class XII education services was in the good category. Satisfaction of class XII students is in the good category. So that similar research can be done by looking at other factors that have an influence on student satisfaction. There is a positive relationship between the quality of education services and the satisfaction of class XII students at Madrasah Aliyah Negeri 2 Karawang. That means, the higher the quality of educational services, the satisfaction of students will increase, and vice versa.